Evaluation of Heavy Metal Accumulation in Sawa Lake Sediments, Southern Iraq using Magnetic Study - Ameen, Nawrass; Rasheed, Laith; Khwedim, Kareem (Iraqi Journal of Science, 2019)
Heavy metal contamination comprises a great concern in the environment. A magnetic study combined with heavy metal analyses was performed in the Sawa Lake in Al-Muthanna governorate (southern Iraq). Concentrations of selected heavy metals (Cr, Fe, Ni, As and Pb) have been measured and magnetic susceptibility (χ) of sediment samples collected from the lake bottom was calculated.The results confirmed that a cement plant, which is located less than two kilometers away from the lake has no contamination levels on the lake’s sediments. No enhancement in the magnetic susceptibility was observed. X-ray florescence (XRF) was performed for heavy metal analyses.Spatial variations of χ with the mean value of 4.58 x 10−8 m3kg−1 and results of other magnetic parameters suggest the magnetic carriers are a predominantly hard magnetic phase like hematite and the existence of small super-paramagnetic proportions. XRF analyses show average concentrations of (Cr, Fe, Ni) and very low for (As, Pb) which is typical for relatively clean areas. Magnetic susceptibility was insignificantly correlated with heavy metals due to low concentrations of both magnetic signals and heavy metal contents. This study has shed some light on the importance of applying the χ measurements techniques to monitor and assess lakes sediment pollution.